An application of probit analysis to factors affecting small-scale farmers' decision about credit - Sebopetji, Thabiso Oscar (My University, 2008)
This paper used primary data collected from 73 small-scale farmers (16 borrowers and 57 non-borrowers) in the Greater Letaba Local Municipality (GLLM) of Limpopo Province of South Africa. The general objective of the study is to analyze farmer-household characteristics that may influence farmers’ decision about whether or not to use credit. Maximum Likelihood Probit Model was used to analyze farmer-households characteristics assumed to be affecting small-scale farmers’ decision about credit. The following variables: farmers’ age in years, gender, marital status and farming experience in years have positive significant effect on farmers’ decision to use credit. On the contrary, number of years of formal education and membership to farmers’ association has negative significant effect. The probabilities for each variable were quantified. The study advocates and emphasizes access to credit by small-scale farmers as a major factor in their production process and production efficiency. Training among both borrowers and non-borrowers in identification of profitable projects and the use of credit for agricultural production is recommended. This kind of training may play a major role in stimulating the demand for credit by these farmers.
Thesis (M.Sc.)(Agriculture) --University of Limpopo, 2008.
Keywords: Farmers; Economic conditions of famers; Credit; 630; Farmers-Economic conditions..; Farms, Small scale